Five Years Experience With Meek Grafting in the Management of Extensive Burns in an Adult Burn Center. Issue 1 (February 2019) - Houschyar, Khosrow Siamak; Tapking, Christian; Nietzschmann, Ina; Rein, Susanne; Weissenberg, Kristian; Chelliah, Malcolm Pyles; Duscher, Dominik; Maan, Zeshaan Naeem; Philipps, Hubertus Maria; Sheckter, Clifford Charles; Reichelt, Beate; Branski, Ludwik Krzysztof; et al.
Background: In extensive burn injuries with lack of donor sites for skin grafting, the Meek technique of skin expansion can be an efficient and effective method in covering extensive wounds. The aim of this retrospective study was to present our experience with the Meek technique of grafting. Methods: We performed a retrospective analysis of patients from our burn center who underwent Meek grafting between 2012 and 2016. Demographics, burn details, clinical course, operative management, and outcomes were collected and analyzed from patient records and operative notes. Outcome measures, including graft take rate, complications and need for further surgery, were recorded. Results: Twelve patients had Meek grafting. The average age was 38 years (range: 15-66). The average percent total body surface area burned was 54.3% (range: 31%-77%). Eighty-three percent of grafted areas healed well, and no regrafting was necessary. In the remaining 17%, infection and hematoma were the leading cause of graft failure. Conclusions: Meek grafting constitutes a rapid and efficient surgical approach for the skin coverage of extensive full-thickness burn injuries with limited autograft donor sites.